Dixon's Return : Odd Craft, Part 10. - Jacobs, W. W. (William Wymark), 1863-1943; Owen, Will, 1869-1957 (Salt Lake City, UT : Project Gutenberg, 2004)
"Dixon's Return" by W. W. Jacobs is a humorous short story written in the early 20th century. The narrative centers on the character George Dixon, who is a meek landlord of the Blue Lion pub in Wapping. After enduring relentless mistreatment from his formidable wife, Mrs. Dixon, along with her relatives who exploit his nature, Dixon takes drastic action by running away to sea, undertaking a journey filled with hardships to reclaim his dignity and sense of identity. The story follows George Dixon's transformation after his return from sea, highlighting his struggle against the dominant personalities in his life. Once back home, he finds his wife and her relatives have continued to undermine him, prompting a fierce stand where he asserts his newfound confidence by declaring himself the master of the pub. The narrative concludes with a remarkable shift in dynamics, showcasing how Dixon's experiences have hardened him and changed the respect within his household, ultimately leading to a role reversal where Mrs. Dixon, once the assertive figure, is now a compliant partner. The story combines humor and social commentary on marital dynamics, masculinity, and personal growth, making it a compelling read. (This is an automatically generated summary.)
Release date is 2004-04-01
Produced by David Widger
Keywords: Humorous stories, English; England -- Social life and customs -- Fiction; Sailors -- Fiction